Kajian Akhlak Bertetangga Sesuai Kitab Taysirul Kholaq Pada Jam’iyyah Ibu-Ibu Dusun Kenteng Barat Desa Besowo Kecamatan Kepung Kabupaten Kediri - Havid Alma’ruf (LP3M IAIFA Kediri, 2023)
Morals as a science is the main and substantial subject in Islam, whose study is not limited to human behavior from the physical aspect, but is also tied to the inner aspect and happiness. A study that concerns an important dimension that includes the issue of the goodness and badness of human life in the world, even with regard to life in the future. In the history of mankind, among others, it is stated in the Qur'an that a strong nation is a nation with good morals, on the other hand, a nation collapses when its morals are damaged. in his own research the author chose to use the PAR (Participatory Action Research) method. the results of this study, perform the following steps; The first step we took was that flexible methods and approaches were needed according to the circumstances. because, there is often a gap between planning and practice in the field. the third step is to evaluate the material studies that have been carried out from the beginning to the end to the jam'iyah mothers. This is an effort to find out the extent of the material that has been captured by the mothers after the study of neighboring morals was conducted.